PERTUMBUHAN DAN DAYA SERAP Chlorella vulgaris TERHADAP LOGAM BERAT TIMBAL (Pb) PADA PERAIRAN DALAM SKALA LABORATORIUM - Anggraini, Wa Ode Linda Rahayu; Iba, Wa; Ambardini, Sri (JSIPi (Jurnal Sains dan Inovasi Perikanan) (Journal of Fishery Science and Innovation), 2022)
This research aims to determine the growth of C. vulgaris (based on specific growth rate and biomass productivity) cultured in Walne medium containing different concentration of lead.Â  C. vulgaris ability in absorbing heavy metals Pb was also measured. This study used a complete randomized design experiment with walne media and the addition of varied concentration of lead.Â  Four lead concentrations used were 3, 5, 7 and 9 ppm. Microalgae was cultured for 8 days at 30 psu and 12:12 photoperiod. Increasing density was calculated every other day. Microalgae was harvested by using 1 M NaOH solution to obtain cell biomass. The lead absporption of C.vulgaris was read using an atomic absorption spectrophotometer. Cell density, specific growth rate and biomass productivity were the highest at 3 ppm and the lowest at 9 ppm. Better lead absorption of C. vulgaris cells was observed at 5 ppm than other concentration tested. This research confirmed that C. vulgaris can be used as bioremediation agent to lead contamination in sea water up to concentration of 9 ppm.